Vrednotenje odnosa sila-hitrost-moč s skoki z dodatnimi bremeni pri kolesarjih - Spudić, Darjan (Šport (Ljubljana), 2021)
The aim of the study was to compare variables of the force-velocity-power (F-v-P) relationship and variables obtained during the Wingate test. Ten elite cyclists participated in the study. Within the same day, all subjects performed squat jumps under four conditions (which were assigned relative to participants' body mass) and cycle- ergometer testing. Results were compared using a paired-samples t-test and Pearson correlation coefficient (r). We found statistically significant differences between maximum and average power variables (effect size w2: 0.766-0.932) and between the slope of the F-v curve and the power drop during the Wingate test (w2 = 0.988). Nevertheless, medium-large correlations (r: 0.59-0.85) were found between the results. Anaerobic power and capacity were higher in cyclists who were force-dominant rather than velocity-dominant. Calculating the F-v-P profile in addition to performing the Wingate test provides more accurate information on the anaerobic properties of the leg extensor muscles and allows cyclists to be categorized based on their dominant power production characteristics. In the future, a timeefficient and energy-saving measurement protocol could provide a basis for more accurate definition of training load in resistance training for cyclists, for planning training/competition tactics, and for future studies to optimize the F-v-P profile in cyclists.
Keywords: cycling; force-velocity relationship; kolesarstvo; moč; power output; profila sila-hitrost; skok iz polčepa; sport; squat jump; šport; test Wingate; Wingate test